Nanotechnology in gastrointestinal endoscopy: A primer - Ashish Kumar Jha (Journal of Digestive Endoscopy, 2012)
Nanotechnology is the understanding, control of matter and development of engineered devices in nanometer range (1-100 nm). Nanoparticles have different physicochemical properties (small size, large surface area to volume ratio, and high reactivity) in comparison to bulk materials of the same composition. The nanotechnology has proved its usefulness in early diagnosis, proteonomics, imaging diagnostics and multifunctional therapeutics. Recent studies have shown its role in early diagnosis and targeted therapy of various gastrointestinal disorders such as hepatitis B virus and hepatitis C virus related liver disease, inflammatory bowel disease, gastric ulcer, and malignancy. Application of this technology appears promising in diagnostic and therapeutic endoscopy such as the endoscopic hemostasis of peptic ulcer bleeding, prevention of clogging of plastic stent and advance capsule endoscopy. This article will highlight the basic concepts of nanotechnology and its potential application in gastrointestinal endoscopy.